Intersections of gender and social status exploring records and documents on criminality in the Philippines - Gutierrez, Filomin C. (2006)
The study examines the criminality of men and women through an exploration of records and documents available from 1860 to 1931. It seeks to understand criminality as structured action anchored on the constructs of gender and social status. It considers gender as the primary construct and social status as the attending construct that relate to the extent, clustering and patterning of criminality. These social categories also serve as coordinates by which actors interpret their experiences of criminality, and shape discourses on criminality created by the criminal justice system and the public. It recognizes that records and documents, such as statistical reports and individual cases from the past put together a picture of criminality of men and women. These sources are also constructions attuned to the agenda, emphases, and lapses of the agencies that generate them.The two colonial regimes during the last decades of the Spanish regime and the early part of the American administration handed down criminal codes and a criminal justice system that oriented towards modernism's emphasis on rationality and equality. Efforts to systematically gather data on criminality were carried out as part of the management and control of a colony and as a response to the growth of positivism in the sciences with its premium on empirical data collection. The study harvests from a crime records, narratives from individual criminal episodes (cases), and discourses from the state reports and scholarly publications produced during the period.
"November 2006."
Thesis (Ph.D. Sociology)--University of the Philippines Diliman.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD)
Keywords: Crime -- Sociological aspects -- Philippines; Crime and criminals -- Philippines; Criminal justice, Administration of -- Philippines -- History; Crime -- Philippines